Prosesi Perkawinan Menurut Hukum Adat Melayu Indragiri Hilir Riau sebagai Salah Satu Aset Budaya Indonesia - Ferawati; Erdianto; Martojo (Indra institute Research & Publication, 2023)
The aim of the research is to explore the customary law of the Malay Indragiri Hilir Riau related to marriage customs, because so far the weakness of the Malay customary community is the absence of written documents related to the customs and culture of marriage of the Malay community, so that with the development and changing times, it is possible that the law Malay customs which have only been passed down orally and passed down from generation to generation will erode and disappear from the Malay world. To obtain the necessary data, the researcher used a qualitative descriptive research method with a field research approach. Then the technique for collecting data was carried out by observing the research location, conducting interviews with traditional leaders and religious leaders in the Malay community. The results of this study are that it is possible to inventory customary marriage laws of the Indragiri Hilir Riau community, these findings can be a reference material for the younger generation and people outside the Malay community to find out the local wisdom values ​​of the Malay community related to marriage processions, so that these values ​​will remain its sustainability is maintained as one of the uniqueness and assets of the Indonesian nation.